2011
DOI: 10.1186/1750-1172-6-46
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability of the kyphoscoliotic type of Ehlers-Danlos syndrome (EDS VIA): clinical, molecular and biochemical delineation

Abstract: BackgroundThe kyphoscoliotic type of Ehlers-Danlos syndrome (EDS VIA) (OMIM 225400) is a rare inheritable connective tissue disorder characterized by a deficiency of collagen lysyl hydroxylase 1 (LH1; EC 1.14.11.4) due to mutations in PLOD1. Biochemically this results in underhydroxylation of collagen lysyl residues and, hence, an abnormal pattern of lysyl pyridinoline (LP) and hydroxylysyl pyridinoline (HP) crosslinks excreted in the urine. Clinically the disorder is characterized by hypotonia and kyphoscolio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 20 publications
1
102
1
2
Order By: Relevance
“…Vascular involvement has been described mainly in vascular EDS (type IV; Pepin et al 20 ), although arterial fragility occasionally has been reported in classical, 21 and kyphoscoliotic EDS. 22 Non-progressive aortic root dilatation has occasionally been observed in EDShypermobility type. 23 The vascular manifestations in XL-PH are different from those observed in the hypermobility and classic types of EDS; they can be more extensive, progressive and may involve peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular involvement has been described mainly in vascular EDS (type IV; Pepin et al 20 ), although arterial fragility occasionally has been reported in classical, 21 and kyphoscoliotic EDS. 22 Non-progressive aortic root dilatation has occasionally been observed in EDShypermobility type. 23 The vascular manifestations in XL-PH are different from those observed in the hypermobility and classic types of EDS; they can be more extensive, progressive and may involve peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, vascular complications can also be observed in the kyphoscoliotic type of EDS (EDS VIA), characterized by a deficiency of collagen lysyl hydroxylase 1 and caused by mutations in the PLOD1 gene [Rohrbach et al, 2011]. Unlike the vascular type, this form of EDS is inherited automosal recessively and characterized by progressive scoliosis, muscular hypotonia, tissue fragility with easy bruising, and sometimes cognitive delay [Rohrbach et al, 2011].…”
Section: Ehlers-danlos Syndromementioning
confidence: 99%
“…The diagnosis relies upon the demonstration of an increased ratio of lysylpyridinoline (LP) to hydroxylysylpyridinoline (HP) crosslinks in the urine measured by HPLC, which is a highly sensitive and specifi c test. In the kyphoscoliotic type of EDS, the LP/HP ratio is ~6, whereas normal ratios are ~0.2 [ 57 ]. In EDS spondylocheirodysplastic subtype, the LP/HP is slightly elevated to ~1 [ 42 ].…”
Section: Urine Analysismentioning
confidence: 95%